Potential Neuroprotective Treatment of Stroke: Targeting Excitotoxicity, Oxidative Stress, and Inflammation - Yang, Qianwen; Huang, Qianyi; Hu, Zhiping; Tang, Xiangqi (Frontiers in Neuroscience, 2019)
Stroke is a major cause of death and adult disability. However, therapeutic options remain limited. Numerous pathways underlie acute responses of brain tissue to stroke. Early events following ischemic damage include reactive oxygen species (ROS)-mediated oxidative stress and glutamate-induced excitotoxicity, both of which contribute to rapid cell death within the infarct core. A subsequent cascade of inflammatory events escalates damage progression. This review explores potential neuroprotective strategies for targeting key steps in the cascade of ischemia–reperfusion (I/R) injury. NADPH oxidase (NOX) inhibitors and several drugs currently approved by the U.S. Food and Drug Administration including glucose-lowering agents, antibiotics, and immunomodulators, have shown promise in treatment of stroke in both animal experiments and clinical trials. Ischemic conditioning, a phenomenon by which one or more cycles of a short period of sublethal ischemia to an organ or tissue protects against subsequent ischemic events in another organ, may be another potential neuroprotective strategy for the treatment of stroke by targeting key steps in the I/R injury cascade.